2007
DOI: 10.1002/jmv.20793
|View full text |Cite
|
Sign up to set email alerts
|

Very low density lipoprotein and low density lipoprotein isolated from patients with hepatitis C infection induce altered cellular lipid metabolism

Abstract: Several abnormalities of lipid metabolism, including hypo-beta-lipoproteinemia and liver steatosis are associated with infection by hepatitis C virus (HCV). The aim of this study was to determine whether circulating lipoproteins of patients with HCV infection could directly cause alterations of lipid cellular metabolism. To this end the metabolic response of human monocyte-derived macrophages (HMDM) to very low-density lipoprotein (VLDL) and low-density lipoprotein (LDL), measuring the cholesteryl ester (CE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Derangements in lipid metabolism have been proposed to be due to a variety of mechanisms including impaired assembly and secretion of VLDL as a consequence of the effect of HCV core protein on microsomal transfer protein, alterations in the composition of VLDL and alterations in VLDL and LDL catabolism 27 28. All these effects occur in the liver, thus clearance of HCV infection, which resolves hepatic damage, should also resolve the lipoprotein changes.…”
Section: Discussionmentioning
confidence: 99%
“…Derangements in lipid metabolism have been proposed to be due to a variety of mechanisms including impaired assembly and secretion of VLDL as a consequence of the effect of HCV core protein on microsomal transfer protein, alterations in the composition of VLDL and alterations in VLDL and LDL catabolism 27 28. All these effects occur in the liver, thus clearance of HCV infection, which resolves hepatic damage, should also resolve the lipoprotein changes.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, to the best of our knowledge, its role in the physiology of VLDL/LDL is as yet unknown, probably because it has only recently been associated with VLDL and LDL by proteomic analyses 45 46. Since we recently found that lipoproteins derived from HCV-infected patients induce altered cellular lipid metabolism,25 it is tempting to speculate that the decreased apoA-I level could have a role in this dysmetabolism. Experiments on the biogenesis and on the metabolic properties of apoB-100-containing lipoproteins in the absence of apoA-I, either in presence or absence of HCV proteins, are necessary to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently found that the circulating lipoproteins of HCV-infected patients induce a change in the cellular lipid metabolism of human monocyte-derived macrophages. In these cells the very low-density lipoproteins (VLDL) and low-density lipoproteins (LDL) isolated from HCV-infected patients induce a decrease in the production of cholesterol ester and triglycerides (TG) and an increase in TG production, respectively 25. One possible explanation for this observation is that HCV may directly affect the molecular composition of host circulating lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…We can anticipate two possible advantages of this selection process. First, it is possible that diversion of the VLDL secretion machinery creates an intracellular environment that is optimal for the viral life cycle, i.e., by providing a lipid-rich intracellular environment (31) that facilitates virus assembly and secretion due to reduced lipid export (36,40). Second, it is possible that the molecular anatomy of the particle selected for secretion confers an advantage over the immature infectious particles found in the cells, e.g., by masking viral envelope epitopes with host lipoproteins and limiting immune recognition in infected individuals or by providing cellular ligands permitting efficient binding to cellular coreceptors, such as SR-B1 (5,29) or the LDL receptor (2).…”
mentioning
confidence: 99%